Status epilepticus in immature rats leads to behavioural and cognitive impairment and epileptogenesis - Kubová, Hana; Mares, Pavel; Suchomelová, Lucie; Brozek, Gustav; Druga, Rastislav; Pitkänen, Asla (The European journal of neuroscience, 2004)
It remains under dispute whether status epilepticus (SE) in the perinatal period or early childhood or the underlying neuropathology is the cause of functional impairment later in life. The present study examined whether SE induced by LiCl-pilocarpine in normal immature brain (at the age of 12 or 25 days; P12 or P25) causes cognitive decline and epileptogenesis, and the data were compared to those of rats undergoing SE as adults. Rats in the P12 group had impaired memory (repeated exposure to open-field paradigm) and emotional behaviour (lower proportion of open-arm entries and higher incidence of risk assessment period in elevated plus-maze) when assessed 3 months after SE, although not as severe as in the older age groups. Importantly, video-electroencephalography monitoring 3 months after SE demonstrated that 25% of rats in the P12 and 50% in P25 group developed spontaneous seizures. Only nonconvulsive seizures (ictal activity in hippocampus accompanied by automatisms) were recorded in the P12 group whereas rats in the P25 group exhibited clonic convulsions. The present findings indicate that SE is harmful to the immature brain as early as P12, which might be compared with early infancy in humans.
Keywords: Behavior, Animal; Electroencephalography; Male; kognitivní poruchy; Rats, Wistar; Brain; Maze Learning; elektroencefalografie; Age Factors; mužské pohlaví; potkani Wistar; Body Weight; pilokarpin; status epilepticus; krysa rodu Rattus; bludiště - učení; Pilocarpine; Animals; Status Epilepticus; zvířata; pohybová aktivita; Cognition Disorders; Rats; věkové faktory; Motor Activity; mozek; chování zvířat; tělesná hmotnost